Innovation in the Application of Appropriate Technology and Marketing Strategies for Cashew Products in Kudi Village, Wonogiri Regency - Joko Riyanto; Puji Astuti; Ardian Ozzy Wianto; Resi Intan Penatari; Ari Prasetyo; Dimas Rahadian Aji Muhammad (Unram Journal of Community Service, 2025)
Agricultural and livestock businesses need development towards a better direction. One of the potentials for developing livestock and agricultural businesses is found in Kudi Village, Wonogiri Regency. This area faces challenges such as extreme poverty, susceptibility to landslides, and drought due to its topographical conditions. This program focuses on empowering two main partners, namely Gapoktan Kudi Makmur in the agricultural sector. Situation analysis identified a number of priority issues, including: the cashew processing production process, which is still manual, unhygienic, and high-risk; limited market access and the absence of product standardization. The implementation of community service activities adopts a sequential five-stage methodology, namely socialization, training, technology application, mentoring and evaluation, as well as institutional strengthening to ensure sustainability. Monitoring and evaluation results show significant progress. Notable achievements that have been realized include improvements in the quality and quantity of cashews, the establishment of the 'Kudiro' product brand, increased production capacity, and the diversification of processed cashew products. The conclusion of this community service activity is that an integrative approach combining technology transfer, human resource capacity building, and institutional strengthening has proven effective in creating a sustainable impact. This community service program provides solutions to technical problems at the production level and builds a cashew agricultural economic ecosystem.